2022
DOI: 10.1038/s41598-022-16814-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment modalities on prognosis of patients with metastatic renal collecting duct carcinoma

Abstract: Although patients with renal collecting duct carcinoma (CDC) benefit from surgery, the value of cytoreductive nephrectomy (CNx) for the prognosis of patients with metastatic CDC remains unclear. Hence, in this study, we used data from Surveillance, Epidemiology, and End Results (SEER) registry to investigate the prognostic factors and the impact of CNx on the outcomes in patients with metastatic CDC. Data of 521 patients, diagnosed with CDC between 2000 and 2018, were retrieved from the SEER database. Kaplan–M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Sui et al demonstrated such improved survival through the combination of cytoreductive surgery with chemotherapy or radiotherapy in metastatic CDC patients, compared to cytoreductive surgery alone or chemotherapy/radiation alone [3]. Moreover, Qian et al investigated the signi cance of cytoreductive nephrectomy, using the SEER database [21], demonstrating that cytoreductive nephrectomy independently improved survival outcomes for metastatic CDC patients. The present study supports this theory by revealing that the OS times of CDC patients who were treated with surgery alone or surgery plus chemotherapy were signi cantly longer than chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Sui et al demonstrated such improved survival through the combination of cytoreductive surgery with chemotherapy or radiotherapy in metastatic CDC patients, compared to cytoreductive surgery alone or chemotherapy/radiation alone [3]. Moreover, Qian et al investigated the signi cance of cytoreductive nephrectomy, using the SEER database [21], demonstrating that cytoreductive nephrectomy independently improved survival outcomes for metastatic CDC patients. The present study supports this theory by revealing that the OS times of CDC patients who were treated with surgery alone or surgery plus chemotherapy were signi cantly longer than chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%